The Role of Digital Da'wah in Alpha Generation Character Education: Peran Dakwah Digital Dalam Pendidikan Karakter Generasi Alpha - Reva Ananda Rudiana; Hakimuddin Salim (Academia Open, 2025)
General Background: The rapid advancement of digital technology has transformed communication, education, and religious outreach, particularly affecting younger generations immersed in digital platforms. Specific Background: Generation Alpha, born into a fully digital environment, demonstrates unique behavioral and learning patterns that differ significantly from previous cohorts, requiring new approaches in moral and character education. Knowledge Gap: While many studies have explored digital literacy and character education for Generation Z, few have specifically addressed the Alpha generation in relation to digital da'wah as a medium for Islamic character development. Aim: This study investigates the role of digital da'wah in shaping the character of Generation Alpha through content on platforms like TikTok and YouTube. Results: Findings reveal that digital da'wah significantly contributes to internalizing Islamic values such as faith, discipline, and social responsibility among Generation Alpha, using appealing and contextualized multimedia content. Novelty: This research uniquely integrates Islamic educational values with digital communication strategies tailored to Generation Alpha, highlighting the synergy between moral instruction and modern technology. Implications: The study emphasizes the importance of creative digital strategies in religious education and calls for collaborative roles from educators, parents, and digital content creators to foster holistic character formation in the digital era.Highlight : Digital da’wah effectively integrates Islamic values into the character education of Generation Alpha. Social media platforms like TikTok and YouTube serve as strategic tools for moral learning. Parental and educator involvement is essential for guiding ethical digital engagement. Keywords : Digital Da'wah, Alpha Generation, Character Education, Islamic Values, Technology